6G-enabled open-pit mine security: toward wise evaluation, monitoring, and early warning - Sun, Xiaokun; Shen, Honghao; Jiang, Tingting; Zhang, Peng; Peng, Simiao; Zhang, Shupeng (Frontiers in Earth Science, 2023)
This research paper introduces a fully integrated monitoring and early warning solution tailored for mining regions. By synergizing 6G and GNSS technologies, the system effectively addresses signal transmission challenges in complex environments. The utilization of 6G's highspeed, low-latency, and extensive connectivity capabilities enables efficient communication in these settings. The study focuses on a specific open-pit mine located in a cold region of China, utilizing it as a case study to demonstrate the system's effectiveness in enhancing slope safety through comprehensive monitoring and early warning mechanisms. Apart from considering traditional dump characteristics and external factors, the system also introduces an innovative early warning index for detecting slope changes. Applying the AHP-fuzzy comprehensive evaluation method ensures reliable evaluation results, facilitating slope assessment, monitoring, and early warning procedures in water-rich open-pit mines situated in cold areas.